The Effect of Class Management and Awarding on Learning Motivation for Christian Education and Ethics in Class XI of SMA Negeri 2 Tukka, Tapanuli Regency Middle of Learning Year 2023-2024 - Irwan Lumban Tobing; Oktober Tua Aritonang; Betty Arli Sonti Pakpahan (STIKes Ibnu Sina Ajibarang, 2023)
The objectives of this study are: 1) to determine whether or not there is a positive and significant influence of Class Management on Christian Religious Education Learning Motivation and Ethics in students; 2) to determine whether there is a positive and significant influence on giving awards to students on Christian Religious Education Learning Motivation and Ethics on students; 3) to determine whether there is a positive and significant influence on Class Management and Giving Rewards to students together on Christian Religious Education Learning Motivation and Ethics. The method used in this study is quantitative research method. The population is all grade XI Christian students of SMA Negeri 2 Tukka, Central Tapanuli Regency, which is 78 people and 63 people were sampled using a crejcie table. Data was collected with a closed questionnaire of 65 items. The results of the data analysis showed that: a) the Fvalue of the class management table > the class management table on Christian education learning motivation and ethics was 27.110 > 3.15 thus it was known that there was an influence of class management on the learning motivation of Christian education and ethics of grade XI students of SMA Negeri 2 Tukka Central Tapanuli Regency which was 30.8%, b) Fvalue calculated > Ftable of awards for Christian education learning motivation and ethics which was 9.246 > 3.15 with it is known that there is an influence on the awarding of Christian education learning motivation and ethics of grade XI students of SMA Negeri 2 Tukka, Central Tapanuli Regency, which is 13.2%, c) F grades are calculated > F class management tables and giving awards to Christian education learning motivation and ethics which is 14,670 > 3.15 thus it is known that there is an influence of class management and awarding on Christian education learning motivation and student ethics Class XI of SMA Negeri 2 Tukka, Central Tapanuli Regency, which is 32.8%, thus Ha is accepted and H0 is rejected.